The Possibilities for Genealogy and Local History Research in the Panevėžys Region - Bagdonas, Vytenis (Bibliotheca Lituana, 2019)
The article explores the surviving genealogical information resources of Panevėžys churches – christening, marriages, deaths, and population censuses. On the basis of the data provided in these books, repeating common names in different areas of the Panevėžys are overviewed. The origin of family names and their territorial linkage are suggested. Published ethnographic books are featured to reflect the availability of the genealogical research in Panevėžys vicinity. Relevant name correlations are drawn using Lithuanian State documents, such as the archives of the nobility. A new study of genetic genealogy is introduced, its value to research, and a spectrum of open possibilities it offers for solving otherwise complex kin puzzles. With good judgement and analysis, the reader may find the approach taken here encouraging to further explore the expatriates and peoples with relation of Lithuanian ancestry of the 19th–20th c.
Keywords: Church metrics; genealogy; genetics; origins of names